Is getting an IELTS or CEFR certificate the same as knowing English? - Naimova Aziza Muxammadovna; Umarova Veronika (Genius Journals, 2022)
This article is devoted to the question of whether a certificate of knowledge of the English language is a guarantee that a person really knows the language. The article will also describe the positive properties of acquiring a certificate, some features of obtaining it and reliability of test takers’ results
Keywords: English language; IELTS certificate; CEFR certificate; test